VERBALIZATION OF THE CONCEPTUAL LAYER OF THE CONCEPT «LOVE / ЛЮБОВЬ» IN LOUIS ARMSTRONG'S SONG TEXTS - Plakhova, O.A; Lee, A.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The purpose of the present paper is to carry out the description of the cognitive attributes that form the conceptual layer of the concept "love / любовь" and are verbalized in Louis Armstrong's song texts and to compare them with the meaningful minimum of the concept recorded in English dictionaries. The content of the concept "love / любовь" does not remain unchanged; its content changes, gradually becoming more complex, along with the development of the socio-cultural community, whose conceptsphere part it is. The following nuclear cognitive attributes of the concept are manifested both in Louis Armstrong's song texts and in the dictionary entries: "love is a strong emotional and sexual feeling"; "love is the feeling of liking and caring for someone"; "love is a form of address". Not only a lovely woman can be treated as the object of love and affection, but also favorite things that make life cosy; home as well as Man as the Supreme creation. All this allows us to say that in the jazz discourse extra types of love that have not received detailed explication in the dictionaries are verbalized, such as love for the homeland, love for the Fatherland, and the unconditional love of the Creator for his creation. In addition, the English-language song discourse manifests additional cognitive attributes related to the conceptual layer of the concept "love / любовь", the vast majority of which are positively marked: "love is giving and showing affection to someone who is loved"; "love is enjoyment"; "love is a possession"; "love is devotion"; "love is eternal"; "love transforms everything around"; "love is generous"; "love is a vital part of life"; "love remains as memories"; "love is a power that changes everyone"; "love is jealous"; "love brings pain".